2003
DOI: 10.1177/0146167202250917
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Group Members in Intergroup Interaction: Safety or Vulnerability in Numbers?

Abstract: An experiment examined how low- and high-prejudice dominant group members' (LPs' and HPs') reactions to intergroup contact were affected by whether they were accompanied by fellow ingroup members who exhibited prejudice-relevant behavior. Participants answered questions alone or in a group and then estimated how they were viewed by an observer who was an ingroup or an outgroup member. HPs believed that they were viewed more negatively by an outgroup member in the individual than the group condition. LPs showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…Whereas Blacks, Latinos, and American Indians are stereotyped in terms of intellectual skill, White Americans are stereotyped as being racist (Sommers & Norton, 2006;Vorauer, 2003). Thus, White Americans are likely to experience stereotype threat during interracial interactions or on tasks that they believe will reveal their racial biases.…”
Section: Working Memory As a Proximal Mediator Of Stereotype Threat Ementioning
confidence: 99%
“…Whereas Blacks, Latinos, and American Indians are stereotyped in terms of intellectual skill, White Americans are stereotyped as being racist (Sommers & Norton, 2006;Vorauer, 2003). Thus, White Americans are likely to experience stereotype threat during interracial interactions or on tasks that they believe will reveal their racial biases.…”
Section: Working Memory As a Proximal Mediator Of Stereotype Threat Ementioning
confidence: 99%
“…In this thesis, I argued that negative metaperceptions should be inherently tied to intergroup contact. Specifically, what we think the out-group thinks about our own group should be shaped by the interactions that we have with them (Vorauer, 2003(Vorauer, , 2006Plant & Butz, 2006). In line with my argument, negative contact was directly associated with more negative metaperceptions in addition to old-fashioned and modern prejudice toward Black Americans (Study 1), Mainland Chinese (Study 2), and Muslim Thais (Study 3).…”
Section: Discussionsupporting
confidence: 56%
“…In line with this literature, empirical research has consistently shown that when majority group members believe that out-group members hold negative preconceptions about them, they tend to reciprocate the negative appraisal and exhibit a wide range of discriminatory behaviors (e.g., Devine, Evett, & Vasquez-Suson 1996;Fein & Spencer, 1997;Kramer & Messick, 1998;Richeson & Shelton, 2003;Richeson, Trawalter, & Shelton, 2005;Sigelman & Tuch, 1997;Vorauer, 2003;Vorauer et al, 1998Vorauer et al, , 2000; also see Vorauer, 2006, for a review). Such discriminatory behaviors may appear to be subtle (e.g., avoiding making eye contact with out-group members and dismissing their opinions and ideas) or apparent (e.g., committing hate crimes and engaging in violent acts against out-group members).…”
Section: Negative Metaperceptions As a Novel Dependent Variablementioning
confidence: 88%
See 2 more Smart Citations